2002
DOI: 10.1002/cncr.10368
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of indolent non‐hodgkin lymphoma in patients with type 1 human immunodeficiency virus infection

Abstract: BACKGROUND There is recent evidence that the incidence of indolent non‐Hodgkin lymphoma (NHL) appears to be increased in persons with the acquired immunodeficiency syndrome (AIDS). The current study was conducted to describe the clinical, immunologic, and pathologic characteristics of indolent B‐cell lymphoma in patients infected with the human immunodeficiency virus (HIV). METHODS The current report was a retrospective study of 10 cases of indolent NHL identified from the AIDS‐Lymphoma Registry at the Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Our case of splenic marginal zone B cell lymphoma confirms the typical features reported for indolent lymphomas in HIV-positive patients in comparison to HIV-positive aggressive lymphomas (bone marrow involvement and higher CD4 cell counts) and to HIV-negative indolent lymphomas (male prevalence, younger age at onset, B symptoms) [3]. In the largest series of splenic marginal zone lymphoma reported so far [5], median age at onset was 64 years with a slight prevalence of females; B symptoms were present in only 20% of patients.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Our case of splenic marginal zone B cell lymphoma confirms the typical features reported for indolent lymphomas in HIV-positive patients in comparison to HIV-positive aggressive lymphomas (bone marrow involvement and higher CD4 cell counts) and to HIV-negative indolent lymphomas (male prevalence, younger age at onset, B symptoms) [3]. In the largest series of splenic marginal zone lymphoma reported so far [5], median age at onset was 64 years with a slight prevalence of females; B symptoms were present in only 20% of patients.…”
supporting
confidence: 88%
“…Lymphoma is one of the most frequent HIV-related neoplasia; in HIV patients, various types of lymphoma can occur, frequently including aggressive B cell lymphoma (i.e., diffuse large B cell lymphoma, Burkitt's lymphoma, plasmablastic lymphoma, and Hodgkin's disease) often with primary extranodal clinical presentation (primary effusion lymphoma and primary central nervous system lymphoma) [1,2]. In contrast, indolent lymphomas are much rarer and only a few cases of mucosa-associated lymphoid tissue lymphoma have been described in both pediatric and adult patients with HIV infection [3][4][5]. Levine et al [3] reported from the AIDS Lymphoma Registry at the University of Southern California ten cases of indolent non-Hodgkin lymphoma with only one case of marginal zone lymphoma (MZL).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Epstein-Barr virus has been identified as a potential factor in the development of gastric lymphomas (11,12). HIV type 1 patients with indolent lymphoma (including MALT) were found to have more CD4+ lymphocyte (13). All antibodies to viruses were found to be negative in our patient.…”
Section: Discussionmentioning
confidence: 60%